Analisis Produktivitas Kegiatan Dredging pada Area Jetty dan Turning Basin Terminal Umum Tanjung Pakis - Chintya Meilinda Puspita Sari; Dian Junita Arisusanty; Femmy Asdiana; Trisnowati Rahayu (Pusat riset dan Inovasi Nasional, 2025)
The dredging activity at Tanjung Pakis General Terminal is carried out to support the construction of the jetty and the deepening of turning basin to enhance the berthing capacity of ships. However, the actual dredger volume did not meet the meet the initial plan, potentially affecting maritime safety and security. This study aims to analyze dredging productivity and identity the factors causing discrepancies between the planned and actual dredging volumes. This study employs a mixed methods approach, combining quantitative analysis through descriptive statistics and qualitative analysis using a fishbone diagram. The research findings indicate a significant decline in dredged volume, with the total realized volume reaching only 221.619,47 m3 out of the planned 500.000 m3. The primary factors contributing to this discrepancy include administrative issues, environmental factors such as high waves, and fishing activities in the area.